2011
DOI: 10.1128/iai.01156-10
|View full text |Cite
|
Sign up to set email alerts
|

BB0844, an RpoS-Regulated Protein, Is Dispensable for Borrelia burgdorferi Infectivity and Maintenance in the Mouse-Tick Infectious Cycle

Abstract: The genome of Borrelia burgdorferi, the causative agent of Lyme disease, is comprised of a large linear chromosome and numerous smaller linear and circular plasmids. B. burgdorferi exhibits substantial genomic variation, and previous studies revealed genotype-specific variation at the right chromosomal telomere. A correlation has also been established between genotype and invasiveness. The correlation between chromosome length and genotype and between genotype and invasiveness suggested that a gene(s) at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…3). As expected, the transcript level of ospC, as well as the transcript levels of several other RpoS-dependent genes, including bb0680, bb0844, bba07, and bba73, were greatly reduced in the plzA mutant in comparison to the wild-type and the complemented strains (7,45,53,54) (Fig. 3).…”
Section: Construction Of the Plza Mutant And The Complemented Strainsmentioning
confidence: 65%
“…3). As expected, the transcript level of ospC, as well as the transcript levels of several other RpoS-dependent genes, including bb0680, bb0844, bba07, and bba73, were greatly reduced in the plzA mutant in comparison to the wild-type and the complemented strains (7,45,53,54) (Fig. 3).…”
Section: Construction Of the Plza Mutant And The Complemented Strainsmentioning
confidence: 65%
“…Recent research investigating borrelia-vector interactions have focused on inactivation of global regulators, individual genes, and replicons to advance our understanding of B. burgdorferi tick colonization and persistence and vector transmission mechanisms (1,4,7,18,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). The loss of BBA66 activity did not completely abolish the ability of B. burgdorferi to invade the host by tick bite (at least when more than 4 ticks/mouse fed to repletion), but mouse infectivity was significantly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the identified promoters have been described elsewhere, demonstrating the validity of the screen. Interestingly, all in vivo-induced promoters identified here have been shown to be a part of the mammalian-induced Rrp2-RpoN-RpoS regulon [Banik et al, 2011;Boardman et al, 2008;Caimano et al, 2004Caimano et al, , 2007Coleman and Pal, 2009;Ouyang et al, 2008;Yang et al, 2005]. This is consistent with the fact that products of RpoS-dependent genes such as ospC are not readily detected in our hands during standard in vitro culture [Casselli et al, 2012 and data not shown] but require shifting from 'tick-like' culture conditions (23 ° C) to 'mammalianlike' culture conditions (37 ° C) for maximal in vitro expression [Burtnick et al, 2007;Caimano et al, 2007].…”
Section: Discussionmentioning
confidence: 99%